2016
DOI: 10.1002/cbdv.201600040
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from the Stems of Daphne holosericea (Diels) Hamaya

Abstract: Two new compounds, one flavanol dimer dapholosericol A (1) and one tigliane diterpene dapholosericin A (2), together with ten known ones, were isolated from the AcOEt extract of Daphne holosericea (Diels) Hamaya. Their structures were elucidated by their spectroscopic data analysis. Compounds 1 and 2 showed moderate activities against acetylcholinesterase with inhibition ratio of 36% and 29% at a concentration of 100 μmol/l, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Further LC-MS-guided fractionation and separation of the EtOAc fraction using ODS and silica gel column chromatography (CC) as well as preparative HPLC led to the isolation of eight tigliane-type diterpenoids ( 1 – 8 ), which were detected in the above LC-MS analysis (Figure ). Six known compounds were identified as wikstrocin A ( 3 ), wikstrocin B ( 4 ), dapholosericin A ( 5 ), , stelleracin E ( 6 ), stelleracin C ( 7 ), and 12- O -benzoylphorbol 13-octanoate ( 8 ) based on detailed spectroscopic analysis and literature data comparison (Figure ). Notably, the known tiglianes 3 – 8 occur infrequently in the plant kingdom, with 3 and 4 obtained from Wikstroemia scytophylla , 5 from Daphne holosericea and W .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further LC-MS-guided fractionation and separation of the EtOAc fraction using ODS and silica gel column chromatography (CC) as well as preparative HPLC led to the isolation of eight tigliane-type diterpenoids ( 1 – 8 ), which were detected in the above LC-MS analysis (Figure ). Six known compounds were identified as wikstrocin A ( 3 ), wikstrocin B ( 4 ), dapholosericin A ( 5 ), , stelleracin E ( 6 ), stelleracin C ( 7 ), and 12- O -benzoylphorbol 13-octanoate ( 8 ) based on detailed spectroscopic analysis and literature data comparison (Figure ). Notably, the known tiglianes 3 – 8 occur infrequently in the plant kingdom, with 3 and 4 obtained from Wikstroemia scytophylla , 5 from Daphne holosericea and W .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the known tiglianes 3 – 8 occur infrequently in the plant kingdom, with 3 and 4 obtained from Wikstroemia scytophylla , 5 from Daphne holosericea and W . scytophylla , , and 6 – 8 from Stellera chamaejasme . The two previously unreported tiglianes were named as wikstrocin D ( 1 ) and wikstrocin E ( 2 ), and their structures were elucidated as described below.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, few studies in the literature have evaluated the potential neuroprotective activity of Daphne species [17,18]. Dapholosericol A and dapholosericin A isolated from the stems of D. holosericea exhibited moderate inhibitory effects with percentage inhibition of 36 and 29%, respectively, at the concentration of 100 µmol/L [17]. The methanol extract of D. mucronata showed a weak AChE inhibitory activity (8.2% at 300 µg/mL) [18].…”
Section: Discussionmentioning
confidence: 99%
“…The known tigliane diterpenoids were identified as dapholosericin A ( 4 ), stelleracin E ( 5 ), and stelleracin C ( 6 ) based on detailed spectroscopic analysis and literature data comparison. Compound 4 was previously reported only from Daphne holosericea , while 5 and 6 were found in Stellera chamaejasme . Compounds 4 – 6 were isolated from the Wikstroemia genus for the first time.…”
Section: Resultsmentioning
confidence: 94%
“…The IR absorption revealed the presence of hydroxy (3399 cm –1 ) and α,β-unsaturated ketone (1716 cm –1 ) functionalities. A comparison of the NMR data of compounds 3 and 4 indicated that the compounds likely had the same tigliane skeleton but different acyl moieties . The presence of two aliphatic ester moieties in 3 were suggested by observation of two ester carbonyl carbon resonances at δ C 173.5 (C-1′) and 176.4 (C-1″), two terminal methyl triplets at δ H 0.88 (H-6′) and 0.87 (H-8″), as well as a series of aliphatic methylene multiplets at δ H 1.27–2.32.…”
Section: Resultsmentioning
confidence: 99%